Mikroenkapsulasi Oleoresin Bawang Putih Menggunakan Ekstruder Ulir Ganda - Aditya Prayoga; Christofora Hanny Wijaya; Azis Boing Sitanggang (Jurnal Teknologi dan Industri Pangan, 2023)
Garlic (Allium sativum) oleoresin is susceptible to damage such as easily volatile and oxidized. It also has low solubility in water. Microencapsulation process is expected to overcome the disadvantages. The aim of this study was to obtain garlic oleoresin microcapsules through twin-screw extrusion process. The study was done by determining the suited carrier, i.e. β-cyclodextrin, dextrin, or maltodextrin, to be used in the microencapsulation of garlic oleoresin, and determining the optimum garlic oleoresin microencapsulation parameters based on response surface methodology (RSM) using the suited carrier. β-cyclodextrin was found to be the suitable carrier for the garlic oleoresin microencapsulation process using a twin-screw extruder. The usage of maltodextrin and dextrin was not possible due to the high viscosity of the mass observed which led to blockage. The modeling obtained through the RSM showed that the combination of the components (carrier, oleoresin, and water) was not ideal for optimum solubility and surface oil. However, the parameters and optimum formula obtained had good experiment repeatability. The optimum garlic powder obtained through the extrusion process showed low surface oil as much as 2.20% and solubility as much as 33.80%. The microencapsulated product exhibited better quality characteristics than commercial K brand spray-dried garlic powder. The extruded powder had nearly four-fold lower aroma intensity prior to dilution, and nearly three-fold higher aroma intensity when diluted in 60°C water.